EEFFECTIVENESS OF OPERATIONAL MANUALS ON EDUCATION FOR YOUNG WORKERS IN JAPANESE-STYLE HOTELS (Proceedings of the International Conference on Hospitality and Tourism Management, 2023)
Japanese-style hotels (ryokans) play an important role in the tourism sector in Japan. Among overseas people planning to visit Japan, 73% wanted to stay in a ryokan before the COVID-19 pandemic. However, ryokans do not have well-organized training programs for young workers to satisfy the diverse needs of guests. This study examined the educational effectiveness of operational manuals for development of hospitality to satisfy these needs. Questionnaire and interview surveys were conducted at ryokans to examine the educational effectiveness of the manuals, using Kolb's experiential learning model. The questionnaire items were related to the educational effects of the manuals. The target area was a regional city in Ishikawa Prefecture, where the Shinkansen bullet train opened in 2015. An analysis of the survey data on young employee development and the potential value of work manuals for ryokans led to two conclusions. First, partial manuals including an appropriate amount of explicit knowledge were effective in supporting two steps in Kolb’s theory: reflective observation and abstract conceptualization. Second, four elements of updating of manuals: customer needs, opinions of person in charge, opinions of outsiders and regular updates, influenced a presentation of an appropriate quality of explicit knowledge, which can promote abstract conceptualization and support acquisition of tacit knowledge. The study showed the usefulness of utilizing partial manuals in the early stages of training of employees in ryokans. This implies that the representation of explicit knowledge enhances the effectiveness of training. In particular, the partial manuals can facilitate two steps in Kolb’s theory (reflective observation and abstract conceptualization) in the ryokan industry.
Keywords: Japanese-style hotels (ryokans); Young workers; Experiential learning theory; Operational manuals; Explicit knowledge; Tacit knowledge